O nekotorykh postoyanno deistvoyushchikh faktorakh v sovremennoi sportivnoi trenirovke - Zhelyaskov, T. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The author represents his own conception of the progress in the sports training system at the contemporary period of the development in sport and its theoretical and technological basis. He developes a concept of factors permanently acting in modern training and beeing the basis for stable results.